(untitled) (Journal of Chemical Engineering, 2010)
In present study a numerical model for bubble size distribution is developed that considers both breakage and coalescence in turbulent gas liquid dispersion. Two-step mechanisms are considered for both breakage and coalescence of bubbles. The bubble breakage is structured as the product of the bubble-eddy collision frequency and breakage efficiency in gas-liquid dispersions. The coalescence function considers the product of bubble-bubble collision frequency and coalescence efficiency. The model overcomes several limitations observed in previous efforts such as empirical parameters, narrow range of operating conditions, and narrow range of geometries. Favorable agreement is found between the predicted bubble size distribution and the experimental data reported in the literature. The percentage of error obtained for the average bubble size was found within ± 17%. Journal of Chemical Engineering Vol.ChE 24 2006 25-34